ELECTRONIC STRUCTURE AND ABSORPTION SPECTRA OF CYANINE DYES DERIVED FROM TETRAZOLOISOINDOLES: UDC 547.759.4 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
The electronic structure and absorption spectra of the cyanine dye trazoloisoindole have been investigated. Those dyes have shown to be carbocyanines by their electronic structure however formally are monomethylcyanines. Electron donation properties of the tetrazoloisoindoline residue were defined on Ilchenko's scale.
Keywords: cyanine dyes, tetrazoloisoindole, Ilchenko's scale